Factors associated with biliary atresia in children with cholestasis in Surabaya - Fina Yusriy Yana; Rendi Aji Prihaningtyas; Sjamsul Arief; Bagus Setyoboedi (Romanian Journal of Pediatrics, 2023)
Introduction. Biliary atresia (BA) represents a progressive and obstructive fibrotic cholangiopathy, serving as a leading cause of liver failure and pediatric liver transplantation worldwide. Identifying risk factors associated with BA incidence is crucial for expediting diagnosis; however, limited research has been conducted in Indonesia. This study aims to investigate the characteristics and analyze the factors associated with the occurrence of BA. Methods. A retrospective observational analysis of medical records encompassing 523 cholestatic patients at the Pediatric Hepatology Outpatient Department and Pediatric Ward of “Dr. Soetomo” General Academic Hospital, Surabaya, from 2011 to 2022 was conducted. The data was segregated into BA and non-BA groups, and diagnostic chi-square tests were employed to determine interrelationships among variables. Subsequently, logistic regression analysis was performed to identify the most impactful variable. Results. Notably, age at first time visiting specialist (p = 0.003), gestational age (p <0.001), birth weight (p = 0.039), and domicile (p = 0.028) exhibited substantial associations with BA. Moreover, gestational age emerged as the most influential factor (p = 0.004). Infants with normal birth weight (≥2,500 grams) exhibited the strongest factor associated factor of BA cholestasis. Conclusion. Initial specialist consultations were predominantly observed within the 0-6 months age range, while term infant and normal birth weight were linked to a higher likelihood of BA cholestasis. Residence in rural areas exhibited a significant correlation with BA incidence.